2021
DOI: 10.1038/s41598-021-97762-x
|View full text |Cite
|
Sign up to set email alerts
|

Compound climate extremes driving recent sub-continental tree mortality in northern Australia have no precedent in recent centuries

Abstract: Compound climate extremes (CCEs) can have significant and persistent environmental impacts on ecosystems. However, knowledge of the occurrence of CCEs beyond the past ~ 50 years, and hence their ecological impacts, is limited. Here, we place the widespread 2015–16 mangrove dieback and the more recent 2020 inland native forest dieback events in northern Australia into a longer historical context using locally relevant palaeoclimate records. Over recent centuries, multiple occurrences of analogous antecedent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Observations of mangrove mortality have increased in recent decades, with some individual mortality events exceeding 1000 ha along coastlines (Duke et al, 2017). These mortality events have corresponded with periods of severe heat, leading to the hypothesis that rising temperature exacerbates impacts associated with elevated hypoxia and salinity (Allen et al, 2021; Lovelock et al, 2017). This is consistent with observations and predictions from upland forests, which suggest that rising temperature, and in particular rising vapor pressure deficit (VPD), is driving increasing tree mortality (McDowell et al, 2020; Williams et al, 2013).…”
Section: Patterns Of Woody‐plant Mortality In Coastal Ecosystemsmentioning
confidence: 99%
“…Observations of mangrove mortality have increased in recent decades, with some individual mortality events exceeding 1000 ha along coastlines (Duke et al, 2017). These mortality events have corresponded with periods of severe heat, leading to the hypothesis that rising temperature exacerbates impacts associated with elevated hypoxia and salinity (Allen et al, 2021; Lovelock et al, 2017). This is consistent with observations and predictions from upland forests, which suggest that rising temperature, and in particular rising vapor pressure deficit (VPD), is driving increasing tree mortality (McDowell et al, 2020; Williams et al, 2013).…”
Section: Patterns Of Woody‐plant Mortality In Coastal Ecosystemsmentioning
confidence: 99%
“…The largest mangrove dieback event recorded globally, involving more than 1000 km of mangrove shoreline in the Gulf of Carpentaria ( 11 ) in 2015/2016, has been linked to a weakening of the monsoon wet season, lower than average rainfall, and a temporary decrease in mean sea level ( 10 ). These conditions were driven by an extreme negative phase of the El Niño Southern Oscillation (ENSO) coincident with a positive phase of the Indian Ocean Dipole (IOD) ( 11 , 12 ). However, dieback in the adjacent Arnhem and Great Barrier Reef bioregions was far less severe, despite the similar imposition of the ENSO and IOD events on sea level and climate.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of tree mortality due to climatic extremes such as drought are increasing globally (Van Mantgem et al, 2009;Ganey and Vojta, 2011;Peng et al, 2011;Millar et al, 2012;Allen et al, 2015Allen et al, , 2021Bendixsen et al, 2015;Assal et al, 2016;Gazol and Camarero, 2022). These rising extreme events, along with fires, insects, and timber harvesting, can substantially threaten forest health.…”
Section: Introductionmentioning
confidence: 99%
“…Adams et al (2017) found that widely observed hydraulic failure tends to be one of the most important underlying physiological mechanisms that causes tree death under drought stress. Moreover, there have been many studies of forest declines and tree loss driven by insect outbreaks (e.g., mountain pine beetles) (Meddens and Hicke, 2014;Hicke et al, 2020), fire (Hicke et al, 2016), drought (Klos et al, 2009;Ganey and Vojta, 2011;Yang et al, 2021), and a combination of multiple causal agents (Allen et al, 2021;Knapp et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%